Safety Oversight of Skincare Products Used by Young Adults in Urban Nigeria: A Systematic Review - Divine Jane Ndako (INTERNATIONAL JOURNAL OF HEALTH AND PHARMACEUTICAL RESEARCH, 2026)
This study examines the safety oversight of skincare products used by young adults in urban Nigeria, with a specific focus on Ikeja, Lagos State. Due to social influences, changing beauty standards, and more market access, young adults are using skincare products more frequently, which has led to serious public health concerns. This conceptual review summarizes the body of research on consumer behavior, regulatory frameworks, skincare product safety, and risk factors related to the use of dangerous products. The ubiquity of unregulated and counterfeit goods, the availability of dangerous substances like mercury, hydroquinone, and corticosteroids, and the role of unofficial markets and internet platforms in promoting their dissemination are all given special emphasis. The study explores further into the oversight role of institutions like the National Agency for Food and Drug Administration and Control (NAFDAC) and highlights concerns including weak enforcement, limited consumer awareness, and inadequate monitoring systems. Results show that consumer knowledge, cultural norms, and market dynamics all have an impact on safety oversight in addition to regulatory measures. In order to promote product safety and protect the health of young adult consumers in urban areas, the study emphasizes the significance of improved regulatory enforcement, improved public awareness, and cooperative stakeholder involvement.